Photophysical Properties of a Newly Synthesized Bichromophoric Polymer for Fe(III) Sensing. Issue 1 (15th October 2013) - Yang, Lifang; Hu, Yulin; Lu, Chunxi
ABSTRACT: A new kind of bichromophoric poly(acrylamide) covalently linked with norfloxacin (NF) and proflavine (PF) was synthesized. The photophysical properties of the polymer were investigated. Energy transfer from NF to PF was observed in the film state of the polymer but not effective in aqueous solution. Responses of different metal cations on the fluorescence intensity of the polymer solution were investigated. Only Fe 3+ ions exhibited remarkable fluorescence intensity quenching to the polymer. The effect of Fe 3+ on the solution and film of the polymer was investigated in detail. The fluorescence intensity of the bichromophoric polymer exhibited a good linear correlation with the concentration of Fe 3+ . © 2013 Wiley Periodicals, Inc. Adv Polym Technol 2014, 33, 21382; View this article online atwileyonlinelibrary.com . DOI 10.1002/adv.21382